STUDI PENERIMAAN MAKNA DAN PERSEPSI MAHASISWA UNIVERSITAS BUNDA MULIA JAKARTA UTARA PADA MASKOT BI-EM - Rustono Farady Marta (Universitas Bunda Mulia, 2013)
The foundation of Bunda Mulia has succeed in managing University of Bunda Mulia (UBM) as a leading university in North Jakarta. UBM has variety institutional identities, especially mascot that will be the object of this research. Mascot is a new way to socialize UBM’s values through website, POM, doll and other promotion tools.UBM has a dolphin mascot namely “Bi-eM”. ‘B’ is abbreviation from Bunda; meanwhile ‘M’ stands for Mulia. The choice of this mascot is because of the characteristics of dolphin. It is smart, diligent, sincere, and helpful. Furthermore, those positive values can be adapted to Biemers (name for all UBM’s stakeholder).Keywords : reception analysis, meaning, perception, mascot